Assessment of basic physical parameters of current Canadian-American National Hockey League (NHL) ice hockey players - Sigmund, M.; Kohn, S.; Sigmundova, D. (Acta Gymnica, 2016)
Background: Physical parameters represent an important part of the structure of sports performance and significantly contribute to the overall performance of an ice hockey player. Basic physical parameters are also an essential part of a comprehensive player assessment both during the initial NHL draft and further stages of a professional career. For an objective assessment it is desirable to know the current condition of development of monitored somatic parameters with regard to the sports discipline, performance level and gaming position.